An Analysis of Non-English Foreign Language Students’ Problem in Speaking - Afdilla Moulidya; Misnawati; Zuraini (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This research is categorized into a case study used descriptive quantitative methodology because this research was to investigate the factors of the reasons why the students rarely speaking  English. The instruments used to collect the data are speaking test and questionnaires. Based on the analysis of the students’ speaking test, the researcher explained that the average persentage of the speaking test is 17,35 %, the percentage showed that the problems are faced by students was from many aspect, namely : Fluency aspect there were 4,23% of students are not fluently in speaking English. Vocabulary aspect there were 5,76% of students lack of vocabulary in giving an opinion. Grammar aspect  there were 5,84% of students difficulties in mastering grammar. Comprehension aspect there were 7,23% of students understand what people said in English but they do not know how to respon them.  Based on the analysis of the students’ questionnaires, the researcher explained that the average persentage of the quesstionnaire is 3,12%, the percentage showed that the students faced some problems in speaking English, such as :  first, the students are not fluently pronounciation in speaking English. Second, the students are not able in mastering vocabulary or lack of vocabulary when speaking English. And the last the students are lazy to study English because they did not understand about English Lesson.